Modelling of Solar Spectral Radiation in Penang Island on a Digital Elevation Model - Choon Yeap, Eng; San Lim, Hwee; Mat Jafri, Zubir (International Journal of Engineering and Technology, 2019)
Interest has been increasingly focused on the studies of solar radiation across the globe ever since people are more concern about energy conservation. Due to the increment of terrestrial application of solar energy, the scientific interest on solar distribution has expanded from broadband solar energy to its spectral distribution. Measurement of solar radiation with its spectral profile provides knowledge for making important decisions involving resources and energy, agriculture and climate. In remote sensing, the measurement of spectral solar radiation is important for sensor calibration and image enhancement to extract the most information out of a satellite image. The spectral radiation can be measured using spectral radiometer specifically design for measuring solar radiation; however such instruments are expensive and only provide point data which is very limited in most studies. This study aims to provide a rigorous spectral radiation model that predict the spectral solar irradiance in temporal resolution of every minute with spectral range from 350nm to 2200nm under cloudless condition. The parameters used in this model include the distance between sun and earth, time, coordinate, atmospheric interference and terrain effect. Atmospheric sounding data was used in this study to provide the necessary atmospheric parameter in the simulation of solar propagation through the atmosphere. The atmospheric effects considered in this study include Rayleigh scattering, aerosol attenuation and the absorption of water vapor, ozone and uniformly mixed gas. The simulation results were projected onto a digital elevation model to further calculate the effect introduced by the topographic variation and to get a three dimensional solar spectral radiation. The result obtained from this study is compared with spectral solar irradiance data collected during the month of June and July, 2018 with root mean square deviation of 9 watt per meter square at the wavelength of 350nm to 2200nm.Â Â